Current status of PSMA-targeted imaging and therapy - Wang, Hui; Li, GuanNan; Zhao, Jie; Eiber, Matthias; Tian, Rong (Frontiers in Oncology, 2024)
Currently, the incidence of prostate cancer is increasing, and it has become a great threat to men's health. The detection, staging, and follow-up of prostate cancer patients are inseparable from morphology or MRI. However, these do not fully meet the needs of diagnosis and patient management. Particularly, due to the late diagnosis, metastatic castration-resistant prostate cancer (mCRPC) patients usually have poor survival and few options for further effective treatment. Prostate-specific membrane antigen (PSMA), because of its overexpression on prostate cancer cells, has gained interest due to its application in imaging and theranostics field. Several PSMA radioligands have been developed for imaging and treating prostate cancer. Many clinical trials have assessed the efficacy and safety profiles of these radionuclide agents and show promise in patients who have exhausted other standard treatment options. To date, several small compounds for targeting PSMA have been developed and 68 Ga-PSMA-11 and 18 F-DCFPyL have been approved by the United States (US) Food and Drug Administration (FDA) for imaging of prostate cancer. 111 In or 99m Tc labeled PSMA-ligand can guide surgeons searching radioactive metastatic lymph nodes, and 177 Lu or 225 Aclabeled PSMA-ligand can be used for internal radiotherapy.Besides, some molecules for therapeutic application are undergoing different stages of clinical trials. In this review, we present current perspectives on the use of PSMAtargeted imaging and theranostics in prostate cancer. As PSMA-targeted imaging and therapeutics are becoming the standard of care for prostate cancer patients, we emphasize the importance of integrating nuclear medicine physicians into multidisciplinary oncology teams.